Operationalising One Health in Nigeria: Reflections From a High-Level Expert Panel Discussion Commemorating the 2020 World Antibiotics Awareness Week - Achi, Chioma R.; Ayobami, Olaniyi; Mark, Godwin; Egwuenu, Abiodun; Ogbolu, David; Kabir, Junaidu (Frontiers in Public Health, 2021)
Antimicrobial resistance (AMR) poses an important One Health challenge for all countries of the world. As human, animal and environmental health are closely linked, it is essential that interventions targeted at reducing the spread of AMR and those promoting antimicrobial stewardship are conducted with all sectors in mind. Tackling this global slow-moving pandemic (AMR) also requires action and strong commitment from all countries of the world. Nigeria, like many other countries, have made considerable progress in implementing the National Action Plan on Antimicrobial Resistance. The accomplishments and ongoing work led by the National Technical Working Group on AMR is commendable. However, gaps still exist in terms of operationalising One Health interventions for AMR, especially regarding rational antimicrobial use and antimicrobial stewardship. The 2020 World Antimicrobial Awareness Week presented an opportunity to convene a multi-sectoral expert panel from national government agencies, research, academia and the World Health Organisation across the Nigerian One Health space. The panel discussion analysed the progress made so far and identified the barriers and the opportunities for operationalising One Health interventions on AMR. The discussion highlighted poor awareness and the fear phenomenon, driven by technical and socio-economic factors, as a common cross-sectoral denominator at the heart of inappropriate antibiotic use within the country. At the system level, suboptimal use of antimicrobials fuelled by the ease of purchase, poor regulations and insufficient enforcement of prescription-only access to antimicrobials, and limited infection prevention and biosecurity measures resonated as drivers of AMR across One Health sectors in Nigeria. Looking forward, the panel discussion identified substantial investment in the governance of the existing One Health component structures, inclusive bottom-up institutional antimicrobial stewardship that fosters community participation and multi-level cross-sectoral collaborations as the next level strategic imperatives. In this respect is the need for a strengthened One Health infrastructure, including an operational workforce, educational strategies to elevate AMR and rational antimicrobial use into public consciousness, and the use of improved data systems as countermeasures to the challenge of AMR.